Possum come a-knockin' - Van Laan, Nancy; Booth, George, 1926- (New York : Knopf, 1990)
A cumulative tale in verse about a mysterious stranger that interrupts a family's daily routine.
Wilson's Children.
Elem. School Library Collection.
School Library Journal.
3.0
K-3
Keywords: Family life -- Fiction; Opossums -- Fiction; Stories in rhyme; Family life -- Fiction; Opossums -- Fiction; Stories in rhyme; Family life -- Fiction; Opossums -- Fiction; Stories in rhyme